Human vulnerability mapping of chemical accidents in major industrial units in Kerala, India for better disaster mitigation. (October 2019) - Rajeev, Karthik; Soman, Sabitha; Renjith, V.R.; George, Priscilla
Abstract: Oil and Gas industries are one of the prominent industrial sectors in India, which plays a pivotal role in influencing important sections of the economy. The hazards associated with these Major Accident Hazard (MAH) industries include fire, explosion and toxic gas release. The oil and gas plants located in Cochin City, Kerala, India handle many hazardous materials, which can lead to potentially dangerous accidents. The objective of this study was to evaluate and map the population vulnerability and to develop a comprehensive procedure for assessing the risk level of the industrial site using geospatial tools. A detailed survey was carried out in the MAH industries of Kakkanad-Irumpanam-Ambalamugal industrial clusters. With the data obtained, an extensive risk analysis was carried out which includes modelling of various incident outcome cases arising from the hazardous storages. Results obtained from consequence modelling and effect modelling was used to estimate the individual and societal risk at environs of the industrial cluster. With the estimated individual risk, threat zones were identified and mapped using Arc GIS software. This study categorizes the study area into different zones based on individual risks . The individual risk based zone map developed in this study can be used as a decision making tool during emergency management and for land use planning for regions surrounding the industrial areas, which may reduce the death toll during a disaster in future. The proposed study is an operational tool allowing competent authorities, industrialists and risk experts to assess the vulnerability of the industrial area.